Rock blasting and overbreak control. (U.S. Dept. of Transportation, Federal Highway Administration, 1991)
This handbook is specifically designed as a guide to highway engineers and blasting practitioners working with highway applications. It was used as a handbook for the FHWA course of the above title. The handbook is a basic review of explosives and their characteristics, along with explosive selection criteria. Initiations and timing effects as well as patterns are also discussed. A simple step by step procedure is outlined to help the engineer review blasting submittals in a systematic fashion. Airblast and ground vibration are discussed along with methods for evaluation and control. Several solved examples are presented in a manner to simplify the necessary calculations with step by step procedures given where appropriate.